2019
DOI: 10.1002/ptr.6441
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spirulina on glycemic control and serum lipoproteins in patients with metabolic syndrome and related disorders: A systematic review and meta‐analysis of randomized controlled trials

Abstract: The aim of this systematic review and meta-analysis was to evaluate the effects of spirulina on glycemic control and serum lipoproteins in patients with metabolic syndrome (MetS) and related disorders. Two independent authors systematically searched online database including EMBASE, Scopus, PubMed, Cochrane Library, and Web of Science from inception until April 30, 2019. The Cochrane Collaboration's risk of bias tool was applied to assess the methodological quality of included trials. The heterogeneity among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 39 publications
5
16
0
2
Order By: Relevance
“…Thirteen of these studies were excluded because they included an abstract ( N = 5) or a protocol ( N = 1) only, were not published in English ( N = 1), had inappropriate exposures ( N = 2) or outcomes ( N = 1), or did not provide updated data ( N = 2). As a result, 50 systematic reviews and meta‐analyses were included in the final analysis (Figure 1; Amir Shaghaghi et al, 2013; Askari et al, 2019; Azhdari et al, 2019; Chen et al, 2020; Fatahi et al, 2019; Ghaedi et al, 2019; Ghaedi et al, 2020; Glisic et al, 2018; Gui et al, 2016; Hadi et al, 2018, 2020; Hadi, Pourmasoumi, Mohammadi, et al, 2019; Hadi, Pourmasoumi, Najafgholizadeh, et al, 2019; Hallajzadeh et al, 2020; Hamedifard et al, 2019; Han et al, 2019; Hasani et al, 2019; Hemati et al, 2020; Hernández‐García et al, 2019; Heshmat‐Ghahdarijani et al, 2020; Karimian et al, 2019; Khorshidi et al, 2020; Li et al, 2014, 2015, 2020; Maierean et al, 2017; Mansour‐Ghanaei et al, 2018; Mohammadi, Hadi, et al, 2019; Mohammadi, Ramezani‐Jolfaie, et al, 2019; Ostadmohammadi et al, 2019; Pourmasoumi et al, 2018, 2020; Rahmani et al, 2019; Rahmani et al, 2020; Ricci et al, 2010; Ried, 2016; Rocha et al, 2019; Sahebkar, 2014; Sahebkar, Simental‐Mendía, et al, 2016; Sahebkar, Soranna, et al, 2016; Salehi‐Sahlabadi et al, 2020; Serban et al, 2015; Shekarchizadeh‐Esfahani et al, 2020; Taku et al, 2010; Ursoniu et al, 2018; Zhang et al, 2020; Zhang, Yuan, et al, 2016; Zhang, Liu, et al, 2016; Zhu et al, 2017; Ziaei et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen of these studies were excluded because they included an abstract ( N = 5) or a protocol ( N = 1) only, were not published in English ( N = 1), had inappropriate exposures ( N = 2) or outcomes ( N = 1), or did not provide updated data ( N = 2). As a result, 50 systematic reviews and meta‐analyses were included in the final analysis (Figure 1; Amir Shaghaghi et al, 2013; Askari et al, 2019; Azhdari et al, 2019; Chen et al, 2020; Fatahi et al, 2019; Ghaedi et al, 2019; Ghaedi et al, 2020; Glisic et al, 2018; Gui et al, 2016; Hadi et al, 2018, 2020; Hadi, Pourmasoumi, Mohammadi, et al, 2019; Hadi, Pourmasoumi, Najafgholizadeh, et al, 2019; Hallajzadeh et al, 2020; Hamedifard et al, 2019; Han et al, 2019; Hasani et al, 2019; Hemati et al, 2020; Hernández‐García et al, 2019; Heshmat‐Ghahdarijani et al, 2020; Karimian et al, 2019; Khorshidi et al, 2020; Li et al, 2014, 2015, 2020; Maierean et al, 2017; Mansour‐Ghanaei et al, 2018; Mohammadi, Hadi, et al, 2019; Mohammadi, Ramezani‐Jolfaie, et al, 2019; Ostadmohammadi et al, 2019; Pourmasoumi et al, 2018, 2020; Rahmani et al, 2019; Rahmani et al, 2020; Ricci et al, 2010; Ried, 2016; Rocha et al, 2019; Sahebkar, 2014; Sahebkar, Simental‐Mendía, et al, 2016; Sahebkar, Soranna, et al, 2016; Salehi‐Sahlabadi et al, 2020; Serban et al, 2015; Shekarchizadeh‐Esfahani et al, 2020; Taku et al, 2010; Ursoniu et al, 2018; Zhang et al, 2020; Zhang, Yuan, et al, 2016; Zhang, Liu, et al, 2016; Zhu et al, 2017; Ziaei et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Aloe vera , fenugreek, and spirulina were shown to statistically improve lipid profiles and combat hyperglycemia. The mechanisms underlying the regulation of glucose and lipid metabolism were proposed due to the rich contents of polysaccharides and phytosterols in Aloe vera (Zhang, Liu, et al, 2016), the large amounts of 4‐hydroxyisoleucine amino acid, polyphenols, saponin, and gel‐like dissolvable fiber in fenugreek (Heshmat‐Ghahdarijani et al, 2020), and the large amount of fiber, polypeptides, and C‐phycocyanin protein in spirulina (Hamedifard et al, 2019). However, the aforementioned mechanisms were also only based on experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the weight loss was not dose-dependent and was higher in patients with obesity rather than in those with overweight [201]. Many beneficial effects, both on glucose and lipid metabolism and oxidant status, have been described in human studies [200][201][202]. However, no data about the potential role of spirulina on energy expenditure are available; therefore, at present, no compelling evidence on this topic is available.…”
Section: Spirulinamentioning
confidence: 98%
“…In contrast, several studies revealed that 2-4.5 g/day spirulina supplementation significantly reduced the SBP or DBP. [48][49][50][51][52] However, Huang et al, 47 in their meta-analysis, observed that spirulina administration has a beneficial effect on DBP improvement, but not SBP.…”
Section: Ta B L Ementioning
confidence: 99%
“…Indeed, the extant literature posits that spirulina contains phycocyanin and peptides with antihypertensive properties which may be able to decrease the SBP or DBP via increases nitric oxide synthase, inhibition of angiotensin I-converting enzymes and consequently inhibiting renin-angiotensin-aldosterone system. [48][49][50][51][52] However, the effective spirulina dosage and its' mechanism of action on blood pressure are still controversial, and therefore, more clinical trials with a longer length of intervention and suitably powered sample sizes are essential.…”
Section: Ta B L Ementioning
confidence: 99%